Literature review: A gender analysis of climate-induced productive-water insecurity in sub-Saharan Africa - CGIAR GENDER Impact Platform; Joshi, Deepa (International Livestock Research Institute, 2024)
Access to water resources for productive uses is fundamental for sustaining livelihoods, food security, and the socioeconomic well-being of marginalized farmers, including women. However, women are particularly vulnerable as they struggle to access and control the water needed for their livelihoods. Variables such as social norms, gender roles, and limited participation in water governance and decision-making processes as well as historical, economic, systemic, and political factors disproportionately impact women—including regional and local political conflicts and instability, and ecological factors of water stress due to changing climate. This literature review focuses on the gendered use of water for productive use in sub-Saharan Africa (SSA) and aims to examine the critical links between gender, water for productive use, and livelihoods, taking account of diverse sociopolitical contexts in SSA, social and power dynamics, governance practices and structural factors, as well as emergent climate crises. This literature review was conducted using the SPIDER-D framework to guide the research process, the gender-transformative approach (GTA) as the conceptual framework, and the 3M analytical framework to assess the political, economic, institutional, and social factors impacting gendered access to water for productive uses at the macro, meso, and micro levels.